2018
DOI: 10.1186/s12936-018-2474-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the trend of malaria prevalence in Ataye, North Shoa, Ethiopia between 2013 and 2017

Abstract: BackgroundMalaria is one of the major public health problems worldwide. In Ethiopia, there is a significant decline in disease burden; however, the overall trend of malaria prevalence is not studied or well-documented in different localities. Hence, the initiation of this study was to analyse the 5-year trends of malaria prevalence in Ataye, North Shoa, Ethiopia.MethodsA retrospective laboratory record review was conducted in Ataye Hospital, North-Shoa, Ethiopia. Malaria data reported from 2013 to 2017 were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

38
26
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(77 citation statements)
references
References 11 publications
38
26
10
Order By: Relevance
“…The study also showed that the prevalence of malaria was high among males and 15-29 years of age groups over the seven years trend. This was similar to the findings of studies conducted in Addi Arkay health center; Ataye district, North Shoa; and Abeshge, south-central Ethiopia [8,11,14]. This might be due to the fact that productive age groups often engaged in farm activities in the fields.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The study also showed that the prevalence of malaria was high among males and 15-29 years of age groups over the seven years trend. This was similar to the findings of studies conducted in Addi Arkay health center; Ataye district, North Shoa; and Abeshge, south-central Ethiopia [8,11,14]. This might be due to the fact that productive age groups often engaged in farm activities in the fields.…”
Section: Discussionsupporting
confidence: 88%
“…Seasonal fluctuations and high prevalence of malaria were observed in autumn (September to December) and the least prevalence in spring (March to May). This was in line with the findings of studies conducted in Ataye, North Shoa, Ethiopia (by Ethiopian Federal Ministry of Health); Addi Arkay health center (Ethiopia); Abeshge (south-central Ethiopia); and Metema hospital, northwest Ethiopia [8,11,14]. Such high malaria prevalence in autumn (September to December) might be related to the formation of stagnant water after the heavy rain season, favorable temperature, and high vegetation density for mosquito breeding.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…According to retrospective trend analysis of malaria cases done in Ataye District Hospital [11], a total of 31,810 blood films were examined from malaria suspected patients from January 2013 to December 2017. Of the examined blood films, 2,670 (8.4%) were microscopically confirmed malaria cases.…”
Section: Introductionmentioning
confidence: 99%